Encroachment Challenges for the South African National Defence Force: The case of Army Support Base Potchefstroom - Matjane, Motsweleng Lebogang Anthony; Mtshawu, Babalwa; Henrico, Ivan; Richmond, Amy (Scientia Militaria - South African Journal of Military Studies, 2024)
The research examined the issue of informal settlements encroaching on military lands, focusing on the effects on military operations and civilian safety in the Potchefstroom region, particularly at the Army Support Base Potchefstroom and the General de la Rey Training Area. The study assessed the extent of settlement growth around military areas from 2011 to 2020 and its broader implications. Geographic information system (GIS) and remote sensing technologies were employed, with a GIS-based change detection methodology tracking changes in land accessibility due to encroachment. Semi-structured interviews with senior military personnel and former candidates provided qualitative insights using interpretative phenomenological analysis, offering first-hand perspectives on encroachment impacts. The findings revealed significant encroachment by the Marikana and Eleazer Up and Coming Farmers communities, resulting in compromised security, vandalism, and safety risks within military areas. This research highlights the urgent need for policy intervention to protect military lands and prevent further encroachment, ensuring operational integrity and civilian safety. Its innovative combination of GIS analysis and qualitative methods contributes to urban geography, security studies, and governance by offering a comprehensive understanding of these challenges. The study advocates for immediate action by policymakers and stakeholders to address encroachment, safeguard military functionality, and protect affected communities. It provides a foundation for future studies and policy measures in similar contexts, emphasising the importance of integrating geographic and social perspectives to resolve such complex issues.